Secondary aspergillus fumigatus infection associated with coloidal goiter in a black-masked lovebird (agapornis personata) - Marietto-Gonçalves, Guilherme Augusto [UNESP]; Grandi, Fabrizio [UNESP]; Rocha, Noeme Sousa [UNESP]; Filho, Raphael Lucio Andreatti [UNESP] (My University, 2014)
Aspergillosis is caused by fungus of Aspergillus genus. Is a multifactorial secondary disease and occurs mainly to immunodeficiency. Goiter is the name to non-inflammatory and non-neoplasic thyroid growth which affecting the animal metabolism. In this report we describe a case of aspergillosis and colloidal goiter in a male Black-masked lovebird (Agapornis personata) diagnosed by post mortem exam. The bird was presented for examination due to severe respiratory signs. An initial palliative treatment was performed in order to relieve the symptoms. Despite this, the patient came to die without performing additional ancillary tests. On gross exam, a pulmonary nodule was observed from which we were able to isolate Aspergillus fumigatus on microbial culture. Histological assessment revealed pulmonary aspergilosis and colloid goiter. Based on histopathological and microbiological assessments we conclude that infection probably was secondary to colloid goiter.
Keywords: Agapornis personata; Aspergillosis; Avian pathology; Goiter